The HIV Care Cascade Among Individuals Under Community Supervision in Baltimore, Maryland. (July 2017) - Zaller, Nickolas; Gordon, Michael; Bazerman, Lauri; Kuo, Irene; Beckwith, Curt
An estimated one in seven HIV-infected individuals pass through U.S. correctional facilities each year. Transitioning from correctional to community settings may increase HIV treatment interruptions and increase the risk of continued HIV transmission in the community. This study assessed access to HIV providers in the community, antiretroviral treatment, and viral suppression to inform the development of interventions to improve HIV treatment outcomes among individuals involved in community corrections. The sample included 100 individuals under community supervision (probation or parole) in Baltimore, Maryland. While a large proportion of the study sample had undetectable HIV viral loads, 39% did not, and this represents a significant HIV transmission risk. Given the large proportion of individuals involved in the criminal justice system who are under community supervision, community corrections may be an important point of intervention to engage or reengage HIV-positive individuals who are currently out of care.